Male Barn Swallows Tolerate Nestling-Like Courtship Calls of Rival Males - Hasegawa, Masaru (Frontiers in Ecology and Evolution, 2021)
Animals often exhibit conspicuous, and sometimes curious, courtship traits, such as nestling-like courtship display in birds, though modern studies of nestling-like courtship display (and calls) are virtually lacking. An exception is previous experiments on the barn swallow Hirundo rustica, demonstrating that females are equally attracted to playback of two structurally similar calls, nestling-like male courtship calls and nestling food-begging calls. The experiments support the sensory trap hypothesis, i.e. that male signals mimic nestling stimuli to exploit female parental care for nestlings. However, female attraction might not be the sole function of nestling-like traits, and males might also have a sensory bias towards nestling-like traits, in which males would be less aggressive towards characteristics typical of immature individuals. Here, I conducted playback experiments to study the function of nestling-like male courtship calls in the context of male–male interactions. Playback of male courtship songs induced frequent approaches by neighbouring males, while nestling-like male courtship calls or nestling food-begging calls induced fewer approaches, though male responses to the latter two vocalisations increased when approaching the nestling period. The observed pattern indicates that, by mimicking immature individuals, males attract intended signal receivers (i.e. females) while avoiding interference from eavesdroppers (i.e. neighbouring males). This unique function can explain why species with parental care exhibit immature-like behaviour.